(untitled) (Texas Journal of Medical Science, 2022)
In this presented article, it was presented that 5-(p-Aminophenyl) - 1,3,4-oxadiazole-2-tion (conditionally D-111) at doses of 10, 30 and 60 mg / kg when administered orally to white mice with various analyzers, including strychnine (1.2 mg / kg subcutaneously), and also orally in doses of 10 and 30 mg/kg. the anticonvulsant activity of the substance and the comparative drug carbamazepines was studied using a model of convulsive seizure induced using repeated administration of corazole at a dose of 30 mg/kg.The anticonvulsant effects of the compound D-111, carbamazepine and control groups at various doses were studied. Based on the results obtained, the studied substance demonstrated high anticonvulsant activity in convulsive seizures, mainly on the strychnine convulsion model.